1998
DOI: 10.1016/s0014-5793(98)00546-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of functional domains of Wilson disease protein (ATP7B) in Saccharomyces cerevisiae

Abstract: Wilson disease is a genetic disorder of copper metabolism characterized by the toxic accumulation of copper in the liver. The ATP7B gene, which encodes a copper transporting P-type ATPase, is defective in patients with Wilson disease. To investigate the function of ATP7B, wild type or mutated ATP7B cDNA was introduced into a yeast strain lacking the CCC2 gene (v vccc2), the yeast homologue of ATP7B. Wild type and the H1069Q mutant could rescue v vccc2, however, the N1270S mutant could not, reflecting phenotypi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
85
0

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 26 publications
6
85
0
Order By: Relevance
“…Currently, the most frequently used system for analysis of WNDP and its disease-related mutants utilizes a yeast strain, in which the endogenous copper-transporting ATPase CCC2 has been deleted (30). Deletion of CCC2 disrupts copper delivery to the secretory compartment and renders the copper-dependent ferroxidase Fet3 inactive, while expression of WNDP restores the Fet3 activity to some extent (18,31). This elegant assay permits rapid screening of mutants (32), however, the indirect nature of the assay prevents characterization of the molecular mechanism of WNDP.…”
Section: Characterization Of the Wndp Expression In Insect Cells-mentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, the most frequently used system for analysis of WNDP and its disease-related mutants utilizes a yeast strain, in which the endogenous copper-transporting ATPase CCC2 has been deleted (30). Deletion of CCC2 disrupts copper delivery to the secretory compartment and renders the copper-dependent ferroxidase Fet3 inactive, while expression of WNDP restores the Fet3 activity to some extent (18,31). This elegant assay permits rapid screening of mutants (32), however, the indirect nature of the assay prevents characterization of the molecular mechanism of WNDP.…”
Section: Characterization Of the Wndp Expression In Insect Cells-mentioning
confidence: 99%
“…The observed cooperativity could be either due to interactions between different intramembrane copper-binding sites or due to cross-talk between the intramembrane copper-binding site and the site(s) at the N-terminal portion of WNDP. The latter explanation is very appealing since previous studies demonstrated that the deletion/mutations of the 5th and/or 6th Nterminal metal-binding sites inhibited transport activity of WNDP (31,47).…”
Section: Functional Expression Of Copper-atpase Atp7bmentioning
confidence: 99%
“…Mutational studies performed to address the role of the N-WLNP have found that, generally, the domains closest to the membrane seem to be the most important both for the ultimate incorporation of copper into Fet3 in yeast complementation assays and in the copper-dependent translocation of WLNP from the vesicular to the cytosolic membrane (23)(24)(25). However, the mechanism by which these domains acquire copper and then transport it across the vesicular membrane is unknown.…”
mentioning
confidence: 99%
“…Numerous genetic and biochemical studies suggest that the domains are not functionally equivalent. For WND, yeast complementation assays indicate that the sixth domain alone is sufficient for copper loading of Fet3, the yeast homolog of ceruloplasmin (26,27). Furthermore, the second or third metal-binding domain cannot substitute for the sixth domain, supporting distinct functions for the individual domains (27).…”
mentioning
confidence: 99%